2021
DOI: 10.1371/journal.pone.0254333
|View full text |Cite
|
Sign up to set email alerts
|

Using Mindful Attention Awareness Scale on male prisoners: Confirmatory factor analysis and Rasch models

Abstract: Aim This study tested the construct validity (i.e., factor structure) of the Persian Mindful Attention Awareness Scale (MAAS) on a sample of male prisoners. Methods All the participants (mean±SD age = 39.44±7.94 years) completed three scales—the Persian MAAS, the Insomnia Severity Index (ISI), and the 12-item General Health Questionnaire (GHQ-12). Confirmatory factor analysis (CFA) and Rasch analysis with differential item functioning (DIF) were applied to examine the construct validity of the MAAS. Specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…Outfit and infit mean square (MnSq) were also used to test the fit. More specifically, both outfit and infit MnSq between 0.5 and 1.5 indicate good fit, while a value smaller than 0.5 indicates overfit (i.e., redundancy in the latent concept) and a value larger than 1.5 indicates misfit (i.e., out of the latent concept) [ 33 , 34 ]. All the statistical analyses were carried out using R software: the psych package was utilized for internal consistency [ 35 ]; the lavaan package was utilized for CFA [ 36 ]; and the eRm package was utilized for the Rasch analyses [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Outfit and infit mean square (MnSq) were also used to test the fit. More specifically, both outfit and infit MnSq between 0.5 and 1.5 indicate good fit, while a value smaller than 0.5 indicates overfit (i.e., redundancy in the latent concept) and a value larger than 1.5 indicates misfit (i.e., out of the latent concept) [ 33 , 34 ]. All the statistical analyses were carried out using R software: the psych package was utilized for internal consistency [ 35 ]; the lavaan package was utilized for CFA [ 36 ]; and the eRm package was utilized for the Rasch analyses [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Rasch model has the strength of converting ordinal scales (e.g., the five-point Likert scale used in the IES-R) to continuous scales for psychometric testing, regarding if any item in an instrument fits with the underlying construct measured by the instrument. Moreover, the Rasch model identifies whether the ordinal scales follow a monotonic order (i.e., the probabilities of answering a more severe level of PTSD are lower than the probabilities of answering a less severe level of PTSD) [ 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. As such, the Rasch model helps identify potential IES-R items that fit the construct of PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the presence of the unidimensional model is consistent with the theoretical and empirical development of the scale (Brown & Ryan, 2003 ) and with validation studies in Spanish carried out in university students (Caycho-Rodríguez, Ventura-León, et al, 2019 ) and older Peruvian adults (Caycho-Rodríguez et al, 2021 ). In this sense, having a one-dimensional structure can be used as a basis for evaluating mindfulness, as a preliminary step to expanding the concept in several dimensions, taking into account that a one-dimensional structure is easier to study and interpret, compared to one multidimensional structure (Poorebrahim et al, 2021 ). The results of the present study also demonstrated that the MAAS-5 has high reliability, and these findings are in line with previous studies based on samples from different countries (Caycho-Rodríguez et al, 2021 ; Caycho-Rodríguez, García Cadena, et al, 2019 ; Goh et al, 2017 ; Osman et al, 2016 ; Smith et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%